Analisis Performansi Pompa Offloading 50-PA-4501A pada Anjungan Main Stupa - Puji Saksono; Akhmad Nurdin; Gilang Aditya (Indonesian Society of Applied Science, 2021)
The activities of gas well exploitation have some problems. One of the problems is the amount of liquid (water) in the tubing column which obstructing the gas production. One of the ways to overcome the problem is to offload activity. One of the important equipment during offload activities is the offloading pump. An offloading pump is used to transfer liquid (water) from the well that has been collected in a vessel to the trunkline. This study aims to see the changes in the performance of the offloading pump between the initial conditions according to the manufacturer's specifications and the current condition after being used for ± 9 years. The type of pump being tested is a multi-stage centrifugal pump model 20 WUC-2R-19. The performance testing of offload pump is done by varying the discharge valve opening by 25%, 50%, 75%, and 100%. After that, compare the actual pump performance with the corrected data using the affinity law. The test performed during the offload process occur, and the fluid characteristics assume to be constant. The results showed that there was a decrease in performance between the initial operating conditions in 2011 with the actual conditions in 2020. The actual capacity of the pump decreased from 24 m3/h to be 23.45 m3/h. The efficiency of the offload pump decreased from the initial condition of 80% to 7.71%. The decrease in efficiency for 9 years is 2.29% or 0.25% per year.